A Flexible and Wavelength‐Designable Polymer Light‐Emitting Diode Employing Sandwich‐Encapsulation for Wearable Skin Rejuvenation Photomedicine. Issue 24 (12th November 2021) - Kim, Hyuncheol; Choi, Hye‐Ryung; Park, Yongjin; Jeon, Yongmin; Lee, Ho Seung; Jeong, Eun Gyo; Park, Kyoung‐Chan; Choi, Kyung Cheol
Abstract: Organic light‐emitting diodes (OLEDs) and polymer light‐emitting diodes (PLEDs) are considered promising devices in that they are not limited to conventional display devices and can provide versatile functions in photomedicine. Many attempts to replace rigid photomedicine devices with wearable light‐emitting devices are in progress, and OLEDs have shown feasibility with respect to device conformality and photo‐medical efficiency. This paper presents a newly designed flexible optoelectronic device utilizing a wavelength‐designable PLED as an option for realizing disposable photomedicine devices. An optical design based on a multilayer electrode and an additional injection unit is proposed; it allows control of the device peak wavelength without any deterioration of charge injection. Furthermore, a sandwich structure utilizing transferable thin‐film encapsulation enables the PLED to achieve mechanical flexibility, low device heat generation, and sufficient operational lifetime (>8 h). When fibroblasts are irradiated by the wavelength‐designable PLED with a 630 nm peak, cell proliferation and production of type‐I procollagen increase by 25% and 36%, respectively. The change of matrix metalloproteinase‐1 is also evaluated, and it is found to decrease by 23%. Based on these results, the wavelength‐designable PLED induces distinct changes of biological factors. Abstract : Flexible and wavelength‐designable polymer light‐emitting diodes are demonstrated and the in vitro test for human fibroblasts is carried out to prove their feasibility to skin rejuvenation. When fibroblast cells are irradiated by the suggested devices, the fibroblast proliferation and production of type‐I procollagen increase by 25% and 36%, respectively, and the matrix metalloproteinase‐1 decrease by 23%.